Dynamic Behavior Simulation Technology of the Wind Turbine Dragging with Double Motors - MA Rui; MENG Yanfeng; HU Shuju; WU Xiaopeng; ZHANG Jie (Kongzhi Yu Xinxi Jishu)
Wind turbine simulator (WTS) is used in the laboratory to carry out various researches on wind power generation technology. Aiming at the increasing capacity of drag motor and driver caused by the increasing of wind turbine simulation experiment system, a dynamic behavior simulation method of wind turbine based on dual-drag motor was proposed. A wind turbine simulation experiment system based on dual-drag motor was constructed. Synchronous control strategy of the double permanent magnet synchronous motors was researched to balance the load distribution of dual-drag motor and operate WTS reliably and stably, and the running characteristics of wind turbine were tested. Test results show that the dynamic simulation of wind turbine mechanical characteristics can realized by the wind turbine simulation system with two drag motors, and the system stability is good.